Formulation of Antibacterial Liquid Soap Based on Butterfly Pea Flower (Clitoria ternatea L.) Extract with Ultrasound-Assisted Extraction Technique - Pratama, Nofran; Rahayu Purnomo Sari, Kurnia; Rahayu, Budi (Universitas Ahmad Dahlan, 2024)
Butterfly pea flower (Clitoria ternatea L.) exhibits antibacterial properties due to bioactive compounds like phenolics and flavonoids. These compounds were extracted using the UAE (Ultrasound Assisted Extraction) method, which is more efficient than conventional methods. This study aims to address antibacterial resistance by formulating an antibacterial liquid soap using butterfly pea flower extract as the active ingredient. Results showed the liquid soap demonstrated good antibacterial activity and physical stability; however, its pH exceeded skin safety standards. A favorability test involving 20 respondents indicated positive responses regarding texture, aroma, and skin-softening effects. In conclusion, liquid soap containing butterfly pea flower extract has potential as an effective antibacterial product but requires pH improvement to enhance safety.